La Importancia de la motricidad fina en el grado Pre - escolar del Centro Etno-Educativo Integral Rural Kasutalain (2020)
The preschool stage is perhaps the most crucial moment in the integral development of the child. At this age, the senses, both external, sight, hearing, touch, smell, taste, and internal, that is, those that are activated without direct relationship with other objects, are always stimulated and are in full maturation phase. which requires the directed manipulation of objects to develop their motor skills. Since children have the possibility to develop various Skills that are favored as motor performance grows refers to the ability that infants can have when making small and large movements such as crawling, stooping, running and walking, etc. Fine motor skills include more precise movements such as assembling, folding paper, coloring, cutting these movements are carried out through the hand with eye-hand coordination.